Interlayer catalyst Fe-MMT, bipolar membrane containing same and application
By introducing the synergistic effect of the intermediate catalyst Fe-MMT and Na-MMT into the bipolar membrane, the problems of high hydrolysis voltage and low acid-base production efficiency in high-salt wastewater treatment are solved, and more efficient Electrochemical properties and lower energy consumption of high-salt wastewater treatment.
Patent Information
- Application Number
- CN202411224202.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-13
AI Technical Summary
The existing bipolar membranes have problems such as high hydrolysis voltage, poor membrane bonding force and low acid-base production efficiency in high-salt wastewater treatment, which limits their widespread use in industrial applications.
The intermediate layer catalyst Fe-MMT is loaded to the surface of the cation exchange membrane by casting method, and combined with Na-MMT and Fe3+ to improve the hydrolysis efficiency of the bipolar membrane and reduce the transmembrane voltage to form an efficient bipolar membrane.
It significantly improves the acid-base production performance and electrochemical stability of the bipolar membrane, reduces energy consumption, and improves the current efficiency of high-salt wastewater treatment, which is better than existing commercial bipolar membranes.
Smart Images

Figure CN119114076A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane separation and high-salt wastewater resource utilization, and particularly refers to an intermediate layer catalyst Fe-MMT and a bipolar membrane containing the same and application thereof. Background Art
[0002] Bipolar membrane (BPM) is a new type of reactive ion exchange membrane composed of a cation exchange layer (CEM), an anion exchange layer (AEM) and an intermediate layer (IL) connecting the two. The intermediate layer is usually a two-dimensional region where electrocatalytic water dissociation occurs, which gives BPM a unique water dissociation property. H2O is dissociated into H under reverse DC voltage. + and OH - , the two pass through the cation and anion exchange layers respectively and move to the solutions on both sides of the membrane. The H2O consumed in the process is supplemented by diffusion of the solutions on both sides of the membrane. This process is the water dissociation process of BPM. BPM is an indispensable technology for zero discharge of high-salt wastewater due to its unique water dissociation performance. It is easy to integrate with other electrochemical technologies and has important application prospects in the fields of carbon emissions, energy conservation and emission reduction, and comprehensive utilization of resources. The bipolar membranes reported in the existing literature are limited by the high water dissociation voltage, poor membrane bonding, and low acid and alkali production efficiency, which cannot be applied on a large scale in industrial applications. Research and optimization of the bipolar membrane intermediate layer catalyst and the preparation process of the bipolar membrane can improve the acid and alkali production performance and electrochemical stability of the bipolar membrane.
[0003] The applicant has not found any patent document similar to the present application in the domestic patent database. Summary of the invention
[0004] The purpose of the present invention is to provide an intermediate layer catalyst Fe-MMT and a bipolar membrane containing the same and application. The intermediate layer catalyst Fe-MMT provided by the present invention is loaded onto the surface of a cation exchange membrane by a tape casting method to form an intermediate layer, FeCl3 reacts with Na-MMT to perform cation exchange, and MMT reacts with Fe 3+ The synergistic effect improves the water dissociation efficiency of the bipolar membrane, reduces the transmembrane voltage of the bipolar membrane, and improves the acid-base production performance of the bipolar membrane.
[0005] The overall technical concept of the present invention is:
[0006] The intermediate layer catalyst Fe-MMT is prepared by the following method:
[0007] The two are mixed evenly in a mass ratio of FeCl3 powder:Na-MMT powder = 2:10 and then allowed to stand for 10 to 12 hours. Water is added to the material after standing and stirred evenly. The stirred material is dried and calcined at high temperature to obtain the intermediate layer catalyst Fe-MMT.
[0008] Bipolar membrane containing an intermediate layer catalyst Fe-MMT.
[0009] Application of bipolar membrane containing intermediate layer catalyst Fe-MMT in treating high-salinity wastewater.
[0010] Sodium-montmorillonite (Na-MMT) nanoclay has a special three-layer structure, which gives Na-MMT a unique 2:1 layered two-dimensional feature, in which silicon-oxygen tetrahedrons and aluminum-oxygen octahedrons are closely connected through shared oxygen atoms. MMT has good water absorption, expansion and adhesion. Metal cations such as Al on the surface of Na-MMT 3+ 、Si 4+ It is easy to be exchanged by some low-valent ions, which makes the surface of Na-MMT negatively charged and has strong cation exchange capacity.
[0011] As a substance that catalyzes water dissociation in the middle layer of the bipolar membrane, trivalent iron ions have a significant catalytic effect. By loading trivalent iron ions or other forms of iron derivatives into the bipolar membrane, the electrodialysis performance of the bipolar membrane can be significantly improved. The catalytic water dissociation mechanism is as follows:
[0012]
[0013] At the same time, loading trivalent iron ions into the middle layer of the bipolar membrane can increase the electric field strength in the middle layer, and by interacting with water molecules, weaken the internal forces of water molecules, thereby reducing the activation energy of water dissociation.
[0014] The specific technical concept of the present invention also includes:
[0015] The main function of adding water is to wet the powder material. The preferred technical solution is that the amount of water added is 10 to 12 ml.
[0016] The main function of drying in the preparation of the intermediate layer catalyst Fe-MMT is to provide conditions for subsequent high-temperature calcination. To facilitate the implementation of the drying process, the preferred technical solution is that the drying condition is drying at a temperature of 60°C for 6 hours.
[0017] The main purpose of high-temperature calcination is to allow iron ions to exchange with sodium-based montmorillonite. In order to achieve a better reaction effect, the preferred technical implementation method is that the high-temperature calcination temperature is 550°C and the time is 4 hours.
[0018] In order to make the catalyst have a larger specific surface area so as to fully exert its efficacy, a more preferred technical solution is to grind and sieve the dried and high-temperature calcined material to obtain the intermediate layer catalyst Fe-MMT powder.
[0019] The bipolar membrane containing the intermediate layer catalyst Fe-MMT is prepared by the following method:
[0020] A. Adding the intermediate layer catalyst Fe-MMT powder to a 95% by volume ethanol solution and mixing evenly to obtain a dispersed solution of the intermediate layer catalyst Fe-MMT with a volume percentage concentration of 10%;
[0021] B. Cast the dispersed solution of the intermediate layer catalyst Fe-MMT obtained in step A onto the surface of the cation exchange membrane to form an intermediate catalytic layer. The loading amount of the intermediate layer catalyst Fe-MMT is 0.15 mg / cm 2 After the surface of the intermediate layer catalyst Fe-MMT is dried, the anion exchange layer solution is cast onto the surface of the intermediate catalytic layer. After the surface is dried, a bipolar membrane containing a Fe-MMT intermediate catalytic layer is obtained; the casting temperature is 60°C.
[0022] Cation exchange membranes are more common in existing literature reports and commercial products, and the applicant will not elaborate on their specific sources and technical solutions. The loading amount of the catalyst is an important parameter in the chemical reaction process, which directly affects the activity and selectivity of the catalyst, and can also reduce the amount of the catalyst, thereby reducing costs.
[0023] In order to make the catalyst powder have a more uniform particle size and further satisfy the stability of the catalytic effect, it is more preferred that in the step A, the intermediate layer catalyst Fe-MMT is crushed and / or ground and then passed through a 50-mesh sieve.
[0024] In order to make the intermediate layer catalyst Fe-MMT dispersed uniformly in the ethanol solution, it is more preferred that the dispersed solution of the intermediate layer catalyst Fe-MMT in step A is obtained by mixing with an ultrasonic and / or magnetic stirrer for 2 to 3 hours.
[0025] The main purpose of heating during casting is to ensure the film quality and production efficiency, and to prevent the film from deteriorating and cracking. In order to facilitate the above purpose, the preferred technical implementation means is to set a heating plate on the surface of the cation exchange membrane without the intermediate catalyst layer attached during casting in the step B. The heating plate can be an electric heating plate with electric heating wire, electric heating tube, etc. as the heating medium. Because it is an existing commercial product, the applicant will not repeat its structure here.
[0026] In order to make the prepared intermediate layer catalyst have a better effect, a more preferred technical implementation means is that the amount of the dispersed solution of the intermediate layer catalyst Fe-MMT cast onto the cation exchange membrane in step B is 0.15 mg / cm 2 .
[0027] In order to make the dispersed solution of the intermediate layer catalyst Fe-MMT cast onto the cation exchange membrane more uniform and easier to operate, a preferred technical solution is that in the step B, a pipette and / or a pipette gun is used to cast the dispersed solution of the intermediate layer catalyst Fe-MMT onto the cation exchange membrane.
[0028] In order to make the prepared bipolar membrane have high hydrolysis efficiency, low energy consumption and low transmembrane voltage, it is more preferred that the thickness of the cation exchange membrane in the bipolar membrane is 40μm, the thickness of the anion exchange membrane is 50-70μm, and the thickness of the middle layer of the bipolar membrane is 7μm.
[0029] The preparation of anion solution is more common in existing literature reports. To facilitate the preparation of anion solution while ensuring the function of the bipolar membrane, the preferred technical solution is that the anion exchange membrane solution in step B is prepared by the following method:
[0030] The quaternized polyphenylene ether is uniformly dissolved in methanol and N,N-dimethylformamide to obtain an anion exchange layer solution.
[0031] In order to make the quaternary aminated polyphenylene ether dissolve evenly, it is more preferred that the amount of the quaternary aminated polyphenylene ether is 12 g, the amount of methanol is 16 ml, and the amount of N,N-dimethylformamide is 6 ml.
[0032] In order to achieve better high-salt wastewater treatment effect with the bipolar membrane containing the intermediate layer catalyst Fe-MMT, the preferred technical implementation method is that the concentration of Na2SO4 in the high-salt wastewater does not exceed 1 mol / L.
[0033] The substantial features and significant technical advances of the present invention are:
[0034] 1. The intermediate layer catalyst of the present invention has the following technical effects: First, the material used for the catalyst is cheap, and the metal cations on the surface of Na-MMT, such as Al 3+ 、Si 4+ First, it is easily exchanged by some low-valent ions, which makes the Na-MMT surface negatively charged and has a strong cation exchange capacity; second, trivalent iron ions are substances that catalyze water dissociation in the middle layer of the bipolar membrane, and their catalytic effect is significant. By loading trivalent iron ions or other forms of iron derivatives into the bipolar membrane, the electrodialysis performance of the bipolar membrane can be significantly improved; third, loading trivalent iron ions into the middle layer of the bipolar membrane can increase the electric field strength in the middle layer, and weaken the internal forces of water molecules by interacting with water molecules, thereby reducing the activation energy of water dissociation; fourth, the combination of MMT and metal ions can reduce the defects of metal ions that are easy to agglomerate and oxidize, reduce the transmembrane voltage of the bipolar membrane, increase its catalytic performance and the water dissociation efficiency of the bipolar membrane, and improve the acid-base production performance of the bipolar membrane.
[0035] 2. The present invention utilizes the tape casting method to prepare the bipolar membrane. First, the casting amount of the interlayer catalyst Fe-MMT can be adjusted as needed, and the preparation process is simple. Second, heating is used to effectively improve the film quality and production efficiency after tape casting, while preventing the film from deteriorating and cracking.
[0036] 3. The applicant's experiments have confirmed that the bipolar membrane containing the intermediate layer catalyst Fe-MMT can effectively improve the current efficiency in the high-salt wastewater treatment process, which is significantly better than the existing commercial BMP and the bipolar membrane that does not contain an intermediate catalytic layer. Compared with ordinary high-salt wastewater treatment (such as evaporation and crystallization), it can significantly reduce the energy consumption of operating equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a schematic diagram of the bipolar membrane water dissociation principle in the present invention.
[0038] Figure 2 It is a schematic diagram of the process flow of preparing the bipolar membrane in the present invention.
[0039] from Figure 2 It can be seen from the figure that the present invention prepares the bipolar membrane by a casting method.
[0040] Figure 3 It is a schematic diagram of SEM, TEM and EDS of the catalytic material Na-MMT and the intermediate layer catalyst Fe-MMT in the present invention.
[0041] Figure (a) is a scanning electron microscope (SEM) schematic diagram of the catalytic material Na-MMT.
[0042] Figure (b) is a transmission electron microscope (TEM) schematic diagram of the catalytic material Na-MMT.
[0043] Figure (c) is a schematic diagram of the energy spectrum (EDS) of the catalytic material Na-MMT.
[0044] Figure (d) is a scanning electron microscope (SEM) schematic diagram of the intermediate layer catalyst Fe-MMT.
[0045] Figure (e) is a transmission electron microscope (TEM) schematic diagram of the intermediate layer catalyst Fe-MMT.
[0046] Figure (f) is a schematic diagram of the energy spectrum (EDS) of the intermediate layer catalyst Fe-MMT.
[0047] From Figure (d), we can see that the metal ion Fe 3+Distribution on the surface of MMT. From the SEM results of Figure (a) and TEM results of Figure (b), it can be observed that MMT presents a large lamellar morphology, and there is a phenomenon of entanglement between the lamellar particles, which provides conditions for the distribution of metal ions on its surface. Combined with the EDS results of Figure (c), it is shown that the MMT catalytic material contains four elements: Al, Mg, O, and Si, indicating that there is no doping of other elements. The SEM results of Figure (d) and TEM results of Figure (e) show that the intermediate layer catalyst Fe-MMT retains the lamellar morphology of MMT itself. Well-dispersed metal particles can be clearly seen between the lamellar layers. The lamellar layers of MMT effectively protect the metal particles attached to the interlayers, improving the shortcomings of metal agglomeration and oxidation. This distribution is due to the combination of the negative charge of the MMT surface and the electrostatic attraction generated by the metal ions. This electrostatic attraction has a direct impact on improving the catalytic performance, and the loading of the metal component increases the specific surface area of the MMT catalyst, which is conducive to more complete contact of the surface active substances. At the same time, the EDS results of the intermediate layer catalyst Fe-MMT in Figure (f) also prove the successful introduction of the metal element Fe.
[0048] Figure 4 Schematic diagram of the microstructure of the bipolar membrane prepared in the embodiment of the present invention.
[0049] Figure (a) is a schematic diagram of a cross-section of a bipolar membrane using a scanning electron microscope. It can be seen that the prepared bipolar membrane is composed of a three-layer structure, with an anion exchange membrane thickness of 54 μm, a cation exchange membrane thickness of 40 μm, and an intermediate layer thickness of 7 μm.
[0050] Figure (bc) is a schematic diagram of the EDS spectrum of the bipolar membrane. Figure (b) and Figure (c) further show that the prepared bipolar membrane is composed of a three-layer structure, and the middle layer of Example 1 contains Fe, O, Si, and Al ions.
[0051] Figure 5 It is a schematic diagram of the current and voltage test principle of the bipolar membrane prepared in the present invention.
[0052] Figure 5 The experimental area of the bipolar membrane is 9 cm 2 During the test, the bipolar membrane was fixed in the middle of the compartment. The experiment was conducted by an adjustable DC regulated power supply at 0-200 mA / cm 2The test is carried out within the current density range, and the test results can be used to calculate the limiting current of the bipolar membrane by dU / dI. The test solutions used in the compartments on both sides of the bipolar membrane are all NaCl solutions with a concentration of 1 mol / L, and the cathode liquid and the anode liquid are both Na2SO4 solutions with a concentration of 1 mol / L. The Na2SO4 solution is selected to avoid the production of chlorine gas harmful to the human body during the experiment. In order to avoid the influence of electrode reaction on the water dissociation process of the bipolar membrane, two commercial Nafion212 membranes are used to separate the electrode chamber from the acid-base chamber. The test process of Examples 1, 2 and the commercial BPM is to connect the titanium-plated ruthenium electrode sheet to a DC regulated power supply and place it in a compartment to provide a steady flow environment required for the test. The change in voltage on both sides of the membrane is observed after connecting two Ag / AgCl reference electrodes to a digital multimeter.
[0053] Figure 6 It is a schematic diagram of the acid-base generation principle of the bipolar membrane prepared in the present invention.
[0054] from Figure 6 It can be seen that a specific membrane stack structure is constructed, which consists of five membranes, two commercial anionic membranes (AMX), two commercial cathodic membranes (CMX) and one bipolar membrane. The order of arrangement from left to right is CEL, AEL, BPM, CEL, AEL. The cross-sectional area of each membrane is 9cm 2 Existing studies have shown that this combination can reduce the H generated during the electrode reaction. + and OH - The H generated by the water dissociation reaction of the bipolar membrane + and OH - During the experiment, an adjustable DC regulated power supply was used to provide a current density of 50 mA / cm 2 In a constant current electric field environment, 200 ml of 0.5 mol / L Na2SO4 solution was used as the raw material solution in each of the four compartments.
[0055] In order to ensure the accuracy of the test data during the experiment, the H in the acid chamber and the alkali chamber were recorded every 30 minutes. + and OH - The concentration of the membrane stack is recorded at the same time, and the total test time is 180 minutes. By analyzing the changes in acid and base concentrations, the rate of acid and base production (r), current efficiency (η) and energy consumption (E) of the bipolar membrane can be calculated.
[0056] Figure 7 This is a graph showing the voltage and current performance test results of the bipolar membrane in the present invention.
[0057] As shown in Figure (a), through the current and voltage performance tests of implementation cases 1 to 2 and commercial BPM, it is confirmed that the transmembrane voltage of the bipolar membrane prepared in Example 1 is reduced, and the transmembrane voltage is better than the selected commercial bipolar membrane performance. As shown in Figure (b), no second peak appears, so during the test of the bipolar membrane, the bipolar membrane prepared in Example 1 does not generate a second limiting current, which further indicates the hydrophilicity of the intermediate layer of the bipolar membrane.
[0058] Figure 8 It is a graph of the electrochemical impedance spectroscopy test results in the present invention.
[0059] From Figure (a), we can see the equivalent circuit diagram used in the experiment. From Figure (b), we can see that the embodiment has the lowest bipolar membrane water dissociation resistance of 1.41Ω. Using the data in Figure (c), according to formulas (1-1) and (1-2), we can respectively derive the time for the ions in the middle layer of the bipolar membrane of the embodiment to migrate out of the depletion region as 16.97μs, and the depletion region thickness (λ) as 15.72nm.
[0060]
[0061] Where C is the equivalent capacitance in ZView software; ε0 is the vacuum dielectric constant, which is 8.854×10 -12 F / m; ε r is the dielectric constant of the sample, pure water is 80; A ef is the effective contact area, which is 3.14 cm 2 ;f max is the frequency corresponding to the highest point on the y-axis of the Bode diagram; ω max is the angular frequency corresponding to the highest point on the y-axis of the Bode diagram; λ is the thickness of the water dissociation depletion region; Τ tr Represents the time it takes for the ions to migrate out of the depletion region.
[0062] Fig. 9 This is a diagram of the voltage stability test results in the present invention.
[0063] During the voltage stability test, the voltage stability of Examples 1 and 2 and the commercial bipolar membrane were analyzed at a current density of 50 mA / cm 2 After running for 48 hours under the conditions of , it can be seen that the bipolar membrane prepared in Example 1 has the lowest voltage and the smallest variation, and has stability.
[0064] Fig.10 It is a graph showing the test results of the acid-base production performance in the present invention.
[0065] In the process of acid and alkali performance test, the high salt solution selected is a Na2SO4 solution with a concentration of 1 mol / L. It can be seen from Figures (a) to (b) that the acid production concentration of Example 1 reaches 0.22 mol / L and the alkali production concentration reaches 0.237 mol / L after 180 minutes of operation. Figure (c) has a current efficiency of 91.7% and an energy consumption of 3.24 kw·h / kg, which is better than the commercial bipolar membrane and Example 2. DETAILED DESCRIPTION
[0066] The following is a further description of the embodiments of the present invention in conjunction with the accompanying drawings, but it should not be understood as a limitation of the present invention. The protection scope of the present invention shall be based on the contents recorded in the claims, and any replacement of equivalent technical means made according to the specification shall not depart from the protection scope of the present invention.
[0067] Example 1
[0068] The intermediate layer catalyst Fe-MMT in this embodiment is prepared by the following method:
[0069] Weigh 2 grams of FeCl3 powder and 10 grams of Na-MMT powder, mix them evenly and let them stand for 10 to 12 hours, add 10 to 12 milliliters of deionized water and stir evenly, place them in an oven and dry them at 60°C for 6 hours, place the dried material in a muffle furnace and calcine it at 550°C for 4 hours, crush and grind the material obtained by high-temperature calcination, and then pass it through a 50-mesh sieve to obtain the intermediate layer catalyst Fe-MMT powder.
[0070] The preparation method of the bipolar membrane containing the intermediate layer catalyst Fe-MMT is as follows:
[0071] A. Adding the intermediate layer catalyst Fe-MMT powder to a 95% by volume ethanol solution to prepare a solution with a volume concentration of 10%, and mixing for 2 to 3 hours using an ultrasonic and / or magnetic stirrer to obtain a dispersed solution of the intermediate layer catalyst Fe-MMT;
[0072] B. Place an electric heating plate on the back of the glass plate covering the cation exchange membrane. Set the dispersed solution of the intermediate layer catalyst Fe-MMT on the surface of the cation exchange membrane by tape casting at a temperature of 60°C. The amount of the dispersed solution of the intermediate layer catalyst Fe-MMT used during tape casting is 0.15 mg / cm 2 The loading amount of Fe-MMT in the intermediate layer catalyst is 0.15 mg / cm 2The thickness of the intermediate layer catalyst Fe-MMT surface after drying is 7 μm. At a temperature of 60°C, the anion exchange layer solution is cast onto the surface of the intermediate layer catalyst Fe-MMT by a casting method. After the surface is dried, an anion exchange layer with a thickness of 50 μm is formed, thereby obtaining a bipolar membrane containing the intermediate layer catalyst Fe-MMT.
[0073] The cation exchange membrane is a commercially available product, the main material of which is sulfonated polyethersulfone, and the thickness of the cation exchange membrane is 40 μm.
[0074] The anion exchange layer solution is a quaternized polyphenylene ether solution, and the solvent is a mixed solvent consisting of a 95% by volume methanol solution and a 15% by volume N,N-dimethylformamide solution. The amount of quaternized polyphenylene ether used is 1g, the amount of methanol used is 16ml, and the amount of N,N-dimethylformamide used is 6ml.
[0075] The use of ultrasonic waves and / or magnetic stirrers to evenly disperse the solute is a conventional technical means, and the applicant will not elaborate on the parameters thereof here.
[0076] The cross section of the bipolar membrane prepared in this example is shown in FIG. Figure 4 shown.
[0077] Example 2
[0078] The cation exchange membrane and anion exchange layer solution in this embodiment are consistent with those in Embodiment 1.
[0079] The bipolar membrane in this embodiment does not contain an intermediate layer catalyst, and the preparation method is as follows:
[0080] The glass plate covered with the cation exchange membrane was placed on a heating plate, and an anion exchange layer solution was cast on the cation exchange membrane at a heating temperature of 60°C. After the surface was dried, an anion exchange layer with a thickness of 50 μm was formed, thus obtaining a bipolar membrane without an intermediate layer catalyst.
[0081] In order to verify the technical effect of the bipolar membrane prepared by the present invention, the applicant conducted the following tests on the bipolar membranes prepared in Examples 1 and 2 and a commercial bipolar membrane (referred to as commercial BPM, sourced from a product of model TWED-8-20 produced by Shandong Tianwei):
[0082] 1. About transmembrane voltage test
[0083] The test process is shown in Figure 5 , Figure 7 , Fig. 9 And its description, the test results are shown in Table 1 and Figure 8 .
[0084] Table 1 50mA / cm 2 Under the condition of transmembrane voltage
[0085] name Transmembrane voltage (V) <![CDATA[First limiting current (mA / cm 2 )]]> Example 1 0.97 6.74 Example 2 1.72 8.23 Commercial BPM 0.99 6.85
[0086] The test results are as follows: the bipolar membrane prepared in Example 1 has a low transmembrane voltage of 0.97V, which is significantly better than the bipolar membrane in Example 2 that does not contain an intermediate layer catalyst and the commercial BPM, and has no second limiting current, indicating that the intermediate layer of the bipolar membrane prepared in Example 1 has good hydrophilicity and is not dehydrated.
[0087] 2. Electrochemical impedance spectroscopy (EIS) testing
[0088] This test is mainly used to evaluate the electrochemical performance of the bipolar membranes prepared in Examples 1 and 2 and the commercial BPM. The test uses a bipolar chamber glass device with an effective area of 9 cm 2 The electrolyte solution used was a NaCl solution with a concentration of 1 mol / L. The glass device was connected to an electrochemical workstation (Autolab, PGSTAT302N), and a pair of titanium-plated ruthenium electrodes were used to provide current or voltage, and two Ag / AgCl electrodes were used to collect the electrochemical signals of the test samples. The test process used the GalvanostaticFRA impedance mode, and the current density was set to 50 mA / cm 2 , the frequency range is set to 105~0.1Hz. To reduce ion interference, the bipolar membrane needs to be immersed in a NaCl solution with a concentration of 1.25mol / L for 24 hours before testing. The BPM water dissociation resistance (RWDR) and the time (Τ) of ion migration out of the depletion region are obtained by EIS experimental test and Zivew software fitting. tr ) and the depletion region thickness (λ), see Fig. 9 and its description.
[0089] The test results are shown in Table 2. The bipolar membrane prepared in Example 1 has the lowest bipolar membrane water dissociation resistance (1.41Ω) and ion migration time (16.97μs), and its depletion region thickness is 15.72nm.
[0090] Table 2 Electrochemical impedance spectroscopy analysis
[0091] name C(F) λ(nm) <![CDATA[τ tr (μs)]]> <![CDATA[R Ω (Oh)]]> <![CDATA[R WDR (Oh)]]> Example 1 <![CDATA[2.906×10 -6 ]]> 15.72 16.97 0.69 1.41 Example 2 <![CDATA[7.644×10 -6 ]]> 32.03 40.64 0.54 4.42 Commercial BPM <![CDATA[3.093×10 -6 ]]> 15.75 17.20 0.72 1.48
[0092] 3. Electrochemical stability test
[0093] The bipolar membranes prepared in Examples 1 and 2 were used to conduct voltage stability analysis tests with commercial BPM, and the electrochemical stability of the bipolar membranes was monitored by chronopotentiometry in combination with an electrochemical workstation (Autolab). 2The voltage changes of the bipolar membrane were monitored for up to 48 hours at a constant current density. The bipolar membrane area used in the stability test was 3.14 cm 2 During the test, the constant current of the bipolar membrane was provided by connecting the titanium-plated ruthenium electrode to the working electrode of Autolab, and the monitoring of electrochemical stability was tested by connecting the Ag / AgCl electrode to the reference electrode of Autolab.
[0094] The test results are as follows: Fig.10 It can be seen that the voltages of the bipolar membranes prepared in Examples 1 and 2 and the commercial BPM all increased. However, the voltage of the bipolar membrane prepared in Example 1 increased from 0.97V to 1.12V, and that of the commercial BPM increased from 1.21V to 1.49V. This result shows that the metal Fe 3+ The combination with MMT reduces the water dissociation resistance of BPM and improves its electrochemical stability. During the 48-hour experiment, the bipolar membrane prepared in Example 1 did not delaminate, which further verifies the stability of the bipolar membrane prepared in Example 1.
[0095] 4. Acid and alkali production performance test
[0096] See the test process Figure 6 and its description, the test results are shown in Fig.10 .
[0097] 5. Instructions for the application and treatment of high salt water
[0098] In the performance test process of Examples 1 and 2 and the commercial BPM, the high salt solution selected for testing is a Na2SO4 solution with a concentration of 1 mol / L.
[0099] 1. Acid and alkali production process of bipolar membrane
[0100] Water dissociation occurs in the bipolar membrane, and in the bipolar membrane water dissociation electrolytic cell, the bipolar membrane and the external circuit form a closed loop. When a reverse bias is applied to both ends of the bipolar membrane, the bipolar membrane maintains the loop current through ion conduction. Under low electric field strength, only salt ions pass through the bipolar membrane to maintain the current; when the electric field strength is further increased, the salt ion flux entering the interface layer of the bipolar membrane is less than the salt ion flux flowing out of the interface layer, and the current cannot be maintained. The ions in the interface layer are depleted, forming a depletion zone; when the field strength increases to a certain value, the high electric field promotes the occurrence of the second Wien effect, while the water binding rate remains unchanged. Therefore, water dissociation reaction occurs in the interface layer, and the generated OH - and H + The protonation-deprotonation effect of the charged groups on the membrane further promotes the dissociation of water, resulting in H + and OH -The ion flux increased significantly, so water dissociation occurred in the middle catalytic layer of the bipolar membrane. Then, because the solution selected in the acid-base performance test was a Na2SO4 solution with a concentration of 1 mol / L, the solution was electrolyzed into Na + 、SO4 2- , and the H hydrolyzed by the bipolar membrane + With OH - Combine separately to produce NaOH and H2SO4.
[0101] 2. Description of the application and treatment of high salt water
[0102] from Fig.10 It can be seen that with the passage of time, the concentration of acid and alkali gradually increases. At the same time, it can be seen that the bipolar membrane can produce acid and alkali when operating in a Na2SO4 solution environment with a concentration of 1 mol / L, and the concentration of acid and alkali is better than that of commercial BPM, indicating that the middle catalytic layer of the bipolar membrane in Example 1 can handle a Na2SO4 solution with a concentration of 1 mol / L.
Claims
1. Intermediate layer catalyst Fe-MMT, characterized in that Prepared by the following method: The two are mixed evenly in a mass ratio of FeCl3 powder:Na-MMT powder = 2:10 and then allowed to stand for 10 to 12 hours. Water is added to the material after standing and stirred evenly. The stirred material is dried and calcined at high temperature to obtain the intermediate layer catalyst Fe-MMT.
2. The intermediate layer catalyst Fe-MMT according to claim 1, characterized in that The amount of water added is 10 to 12 ml.
3. The intermediate layer catalyst Fe-MMT according to claim 1, characterized in that The drying condition is drying at a temperature of 60° C. for 6 hours.
4. The intermediate layer catalyst Fe-MMT according to claim 1 or 3, characterized in that The high temperature calcination temperature is 550°C and the time is 4 hours.
5. The intermediate layer catalyst Fe-MMT according to claim 1, characterized in that The dried and high-temperature calcined material is ground and sieved to obtain the intermediate layer catalyst Fe-MMT powder. 6 . A bipolar membrane comprising the intermediate layer catalyst Fe-MMT according to claim 1 .
7. The bipolar membrane according to claim 6, characterized in that Prepared by the following method: A. Adding the intermediate layer catalyst Fe-MMT powder to a 95% by volume ethanol solution and mixing evenly to obtain a dispersed solution of the intermediate layer catalyst Fe-MMT with a volume percentage concentration of 10%; B. Cast the dispersed solution of the intermediate layer catalyst Fe-MMT obtained in step A onto the surface of the cation exchange membrane to form an intermediate catalytic layer. The loading amount of the intermediate layer catalyst Fe-MMT is 0.15 mg / cm 2 After the surface of the intermediate layer catalyst Fe-MMT is dried, the anion exchange layer solution is cast onto the surface of the intermediate catalytic layer. After the surface is dried, a bipolar membrane containing a Fe-MMT intermediate catalytic layer is obtained; the casting temperature is 60°C.
8. The bipolar membrane according to claim 7, characterized in that In the step A, the intermediate layer catalyst Fe-MMT is crushed and / or ground and then passed through a 50-mesh sieve.
9. The bipolar membrane according to claim 7, characterized in that The dispersed solution of the intermediate layer catalyst Fe-MMT in step A is obtained by mixing with an ultrasonic and / or magnetic stirrer for 2 to 3 hours.
10. The bipolar membrane according to claim 7, characterized in that In the step B, a heating plate is arranged on the surface of the cation exchange membrane to which the intermediate catalyst layer is not attached during casting.
11. The bipolar membrane according to claim 7, characterized in that The amount of the dispersed solution of the intermediate layer catalyst Fe-MMT cast onto the cation exchange membrane in step B is 0.15 mg / cm 2 .
12. The bipolar membrane according to claim 7, characterized in that In the step B, the dispersed solution of the intermediate layer catalyst Fe-MMT is cast onto the cation exchange membrane using a pipette and / or a pipette gun.
13. The bipolar membrane according to claim 7, characterized in that The thickness of the cation exchange membrane in the bipolar membrane is 40 μm, the thickness of the anion exchange membrane is 50-70 μm, and the thickness of the dried intermediate layer catalyst Fe-MMT is 7 μm.
14. The bipolar membrane according to claim 7, characterized in that The anion exchange membrane solution in step B is prepared by the following method: The quaternized polyphenylene ether is uniformly dissolved in methanol and N,N-dimethylformamide to obtain an anion exchange layer solution.
15. The bipolar membrane according to claim 14, characterized in that The amount of the quaternized polyphenylene ether is 1 g, the amount of methanol is 16 ml, and the amount of N,N-dimethylformamide is 6 ml.
16. Use of the bipolar membrane according to any one of claims 6 to 15 in treating high-salinity wastewater.
17. Use of the bipolar membrane according to claim 16 in treating high-salinity wastewater, characterized in that The concentration of Na2SO4 in high-salt wastewater shall not exceed 1 mol / L.
